Why do contracts differ between VC types? Market segmentation versus corporate governance varieties - Julia Hirsch; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
The main objective of the present paper is to disentangle observed differences in the design of contracts across VC types into firm selection effects and corporate governance differences between VC types (different contracts). Based on a theoretical approach developed in the first part of the paper, we investigate in the second part these issues empirically by using a unique, hand-collected German data set consisting of all contractual details of VC investments into 290 entrepreneurial firms in the period 1990-2004. By employing various matching procedures, we show that VC types differ in both firm choice and corporate governance approach.
urn:nbn:de:hebis:30-27711
Keywords: G24; G32; G34; 330; Venture Capital; Corporate Governance; Matching; Contract Design